Java: The Complete Reference - Schildt, Herbert (McGraw-Hill, 2021)
The definitive guide to Java programming-thoroughly revised for Java SE 17Fully updated for the current version of Java, Java SE 17, this practical guide from Oracle Press shows, step by step, how to design, write, troubleshoot, run, and maintain high-performance Java programs. Inside, bestselling author Herbert Schildt covers the entire Java language, including its syntax, keywords, and libraries. The book lays out cutting-edge programming techniques and best practices.Java: The Complete Reference, Twelfth Edition features clear explanations, detailed code samples, and real-world examples that demonstrate how Java can be put to work in the real world. JavaBeans, servlets, applets, Swing, lambda expressions, multithreading, and the default interface method are thoroughly discussed. You will get full details on all of the new features and functions available in Java SE 17.Designed for novice, intermediate, and professional programmers alikeSource code for all examples and projects are available for downloadWritten in the clear, uncompromising style for which Herb Schildt is famous